2017
DOI: 10.4103/apjon.apjon_35_17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of structured education to patients receiving oral agents for cancer treatment on medication adherence and self-efficacy

Abstract: Objective:This study was conducted to examine the effect of structured education on medication adherence and self-efficacy through the use of the MASCC Oral Agent Teaching Tool (MOATT) for patients receiving oral agents for cancer treatment.Methods:This quasi-experimental study has been conducted at two hospitals; 41 patients were included in the study. Data were obtained using a questionnaire, medication adherence self-efficacy scale (MASES), memorial symptom assessment scale, and a follow-up form (diary). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 47 publications
1
25
1
1
Order By: Relevance
“…The level of self-efficacy of the patients in this study (Table 3) was found to be similar to that from some studies in Asian countries (Masoudiyekta et al, 2018;Tokdemir & Kav, 2017). The increasing F-DMSES scores corroborated the effectiveness of the two message-framed videos on diabetes-management self-efficacy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The level of self-efficacy of the patients in this study (Table 3) was found to be similar to that from some studies in Asian countries (Masoudiyekta et al, 2018;Tokdemir & Kav, 2017). The increasing F-DMSES scores corroborated the effectiveness of the two message-framed videos on diabetes-management self-efficacy.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous factors have been identified as related to nonadherence to treatment regimens, such as complexity of regimens, beliefs regarding drug efficacy, side effects, and drug cost (Fennimore & Ginex, 2017). Although participants in this study reported moderate self-efficacy at the baseline, it is noteworthy that the information delivered in the videos about self-management increased their selfefficacy levels after the intervention (Masoudiyekta et al, 2018;Tokdemir & Kav, 2017).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Nonadherence is more frequent in patients of older age, lower level of education, or lower income and may increase with the distance between home and cancer care facilities. 14 Patient education may be proposed to improve adherence to treatment 15 , 16 but is not available in all areas. 17 , 18 In cases where both oral and intravenous treatment are feasible, 71% of practitioners reported a preference for oral CT in a palliative situation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bandura, the development of self-efficacy is the way to create a target behavior in patients [18]. Educational interventions have been reported as an effective way to improve patients' self-efficacy in specific groups of diseases such as asthma, diabetic foot, chronic kidney disease, and some types of cancer [21][22][23][24][25]. However, there is a gap in studies evaluating the effect of educational intervention on self-management in post-HSCT patients.…”
Section: Introductionmentioning
confidence: 99%